Analisis Semiotika Pada Pakaian Tradisional Jepang Kimono Kurotomesode - Anisa Ayu Darma Putri; Yusida Lusiana; Diana Puspitasari (Janaru Saja: Jurnal Program Studi Sastra Jepang (Edisi Elektronik), 2020)
The purpose of this research is to describe the semiotic meaning (denotation, konotation, and myth) from the characteristics of kimono kurotomesode using Roland Barthes theory of semiotics. This research is a qualitative descriptive research using library research as a methods of data collection and the data source from Japanology Plus video. The result of the analysis amounts five characteristics of kimono kurotomeosode along with the myth that contained in it, there are crest can be a veiled identifier for knowing the origin of the family, basic black color that indicates social status, has a shorter kimono sleeve that only worn by married woman, pine pattern or matsumon which is a symbol of strength and longevity, and obi with a gold color that symbolizes wealth and widely used for things that are considered honorable in religious life. The meaning of myth in kimono will be different for each type of kimono because the meaning of the myth can’t be separated from the cultural context that constructs it. Keywords: kimono, kurotomesode, Roland Barthes’ semiotics